Islam In Southeast Asia - Arfah Ibrahim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
This article will discuss about Southeast Asian Islam. This article describes how the process of Islamic presence in Southeast Asia, the process of dissemination, development, and decline of Islamic teachings itself. Islam is a religion that has now spread to all continents and countries on the surface of this earth. Because indeed in the teachings of Islam itself demands to people who embrace Islam spread it to other people who do not know Islam, in Islam too easy to understand the teachings according to the rational and also a lot of natural proof that Islam is a religion correct. So Muslims who have good morals ease in spreading so that people around nonMuslims want to accept, follow, and convert to Islam.